Inventory of orchid diversity in Merauke District, South Papua Province, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Pammai K, Al Muhdhar MHI, Sari MS, Sueb, Yuhanna WL. 2022. Inventory of orchid diversity in Merauke District, South Papua Province, Indonesia. Biodiversitas 23: 6082-6092. The Orchidaceae is a family with the highest diversity among flowering plants. One of the regions that have high biodiversity is Papua, Indonesia, with an estimate to have around 2869 species of orchids. Nonetheless, such wealth of diversity might be threatened due to habitat loss caused by regional development, thus periodical assessment might be required to see the status of orchid diversity. This study aims to inventory orchids in Merauke, South Papua as Indonesia's natural wealth. We used an exploratory method, collecting samples and documentation, then analyzing the results qualitatively by identifying orchid species using several literature. The results of this study obtained 65 species. Among the species found, there were 10 endemic species to Papua, 19 species included in the IUCN Red List and 65 species included in the CITES list. When compared with the previous study, we also recorded several species which were not documented in the previous study, although there were several species that were no longer found. The absence of some species is likely due to overexploitation and human activities in the form of land conversion which causes a decrease in orchid habitat and changes in the microclimate. Based on this research, it can be concluded that the forest in Merauke District still has the potential to become a natural orchid habitat. However, it should be noted that some human activities can be the cause of the decline in the orchid population in Papua.